Dabigatran initiation in patients with non-valvular AF and first acute ischaemic stroke: a retrospective observational study from the SITS registry. Issue 5 (19th May 2020) - Escudero-Martinez, Irene; Mazya, Michael; Teutsch, Christine; Lesko, Norbert; Gdovinova, Zuzana; Barbarini, Leonardo; Fryze, Waldemar; Karlinski, Michal; Kobayashi, Adam; Krastev, Georgi; Paiva Nunes, Ana; Pasztoova, Katarina; et al.
Abstract : Background and objective: The optimal timing for initiation of dabigatran after acute ischaemic stroke (AIS) is not established. We aimed to evaluate initiation timing and clinical outcomes of dabigatran in AIS patients with non-valvular atrial fibrillation (NVAF). Design: Retrospective study based on prospectively collected data in SITS (Safe Implementation of Treatment in Stroke) Thrombolysis and Thrombectomy Registry from July 2014 to July 2018. Participants: European NVAF patients (≥18 years) hospitalised after first-ever ischaemic stroke. Setting: A multinational, observational monitoring register. Intervention: Dabigatran initiation within 3 months after the ischaemic stroke. Primary and secondary outcomes: The primary outcome was time from first-ever ischaemic stroke (index event) to dabigatran initiation. Additional outcomes included physicians' reasons for delaying dabigatran initiation beyond acute hospital discharge and outcomes within 3 months of index event. Methods: We identified patients with NVAF who received dabigatran within 3 months of the index event. We performed descriptive statistics for baseline and demographic data and clinical outcomes after dabigatran initiation. Results: In total, 1489 patients with NVAF received dabigatran after AIS treated with thrombolysis and/or thrombectomy. Of these, 1240 had available initiation time. At baseline, median age was 75 years; 53% of patients were women, 15% were receiving an oral anticoagulant, 29% acetylsalicylic acid and 4% clopidogrel. Most patients (82%) initiated dabigatran within 14 days after the index event. Patients initiating earlier had lower stroke severity from median NIHSS 8 (IQR 6–13) if initiated within 7 days to NIHSS 15 (9–19) if initiated between 28 days and 3 months. Most common reasons for delaying initiation were haemorrhagic transformation or intracranial haemorrhage, stroke severity and infarct size. Few thrombotic/haemorrhagic events occurred within 3 months after the index event (20 of 926 patients, 2.2% with the available data). Conclusions: Our findings, together with previous observational studies, indicate that dabigatran initiated within the first days after an AIS is safe in patients treated with intravenous thrombolysis, endovascular thrombectomy or both. Trial registration number: SITS Thrombolysis and Thrombectomy Registry (NCT03258645 ).